A new electrochemical sensor based on Fe3O4 functionalized graphene oxide-gold nanoparticle composite film for simultaneous determination of catechol and hydroquinone. (20th December 2015) - Erogul, Seyma; Bas, Salih Zeki; Ozmen, Mustafa; Yildiz, Salih
Abstract: Catechol (1, 2-dihydroxybenzene) and hydroquinone (1, 4-dihydroxybenzene) are two isomers of phenolic compounds which often coexist and interfere with each other during their identification in environmental samples. This study presents simultaneous determination of catechol (CC) and hydroquinone (HQ) using a new electrochemical sensor based on Fe3 O4 functionalized graphene oxide-gold nanoparticle composite (AuNPs/Fe3 O4 -APTES-GO). CV results show well-defined oxidation peaks with anodic peaks at 0.15 V for CC and 0.05 V for HQ, and the peak-to-peak separation for CC and HQ is about 100 mV. Under the optimized conditions, the current response of AuNPs/Fe3 O4 -APTES-GO/GCE is linear for CC and HQ in the range of 2-145 μM and 3-137 μM, respectively. The detection limits for CC and HQ were found to be 0.8 μM and 1.1 μM, respectively. The fabricated sensor was successfully applied for the determination of CC and HQ in tap water sample with satisfactory recovery.